Neostriatum neuronal TRPV1-signalling mediates striatal anandamide at high concentration facilitatory influence on neostriato-nigral dishinhibitory GABAergic connections - da Silva, Juliana Almeida; Almada, Rafael Carvalho [UNESP]; Falconi-Sobrinho, Luiz Luciano; Pigatto, Glauce Regina; Hernandes, Paloma Molina [UNESP]; Coimbra, Norberto Cysne (Elsevier, 2023)
Rationale: Several lines of evidence have demonstrated that the cannabinoid type 1 receptor (CB1) is found in the caudate nucleus and putamen (CPu) in addition to the substantia nigra pars reticulata (SNpr). Here, we investigated the role of endocannabinoid neuromodulation of striato-nigral disinhibitory projections on the activity of nigro-collicular GABAergic pathways that control the expression of unconditioned fear-related behavioural responses elicited by microinjections of the GABAA receptor selective antagonist bicuculline (BIC) in the deep layers of the superior colliculus (dlSC). Methods: Fluorescent neural tract tracers were deposited in either CPu or in SNpr. Wistar rats received injection of vehicle, anandamide (AEA), either at low (50 pmol) or high (100 pmol) concentrations in CPu followed by bicuculline microinjections in dlSC. Results: Connections between CPu, the SNpr and dlSC were demonstrated. The GABAA receptor blockade in dlSC elicited panic-like behaviour. AEA at the lowest concentration caused a panicolytic-like effect that was antagonised by the CPu pretreatment with AM251 at 100 pmol. AEA at the highest concentration caused a panicogenic-like effect that was antagonised by the CPu pretreatment with 6-iodonordihydrocapsaicin (6-I-CPS) at different concentrations (0.6, 6, 60 nmol). Conclusion: These findings suggest that while pre-synaptic CB1-signalling subserves an indirect facilitatory effect of AEA on striato-nigral pathways causing panicolytic-like responses through midbrain tectum enhanced activity, post-synaptic TRPV1-signalling in CPu mediates AEA direct activation of striato-nigral disinhibitory pathways resulting in increasing dlSC neurons activity and a panicogenic-like response. All these actions seem to depend on the interface with the nigro-collicular inhibitory GABAergic pathways.
Keywords: Anandamide; Caudate nucleus; Deep layers of superior colliculus; Endovanilloid receptors; Striatonigral-nigrotectal GABAergic pathways; Unconditioned fear